The world food situation and prospects to 1985 - United States. Department of Agriculture (Washington, D.C. : Economic Research Service, U.S. Dept. of Agriculture, 1974)
The book analyses the patterns of world food production, consumption, prices and trade in the two decades prior to 1972 in terms of their effect on the turbulent world food situation of 1972-74.
Cover title.
Includes bibliographical references.
usc 15/04/2019
Ref
Keywords: Food supply; Food relief; Malnutrition